BRIDGING THE GAP BETWEEN R&D AND COMMERCIALIZATION IN PHARMACEUTICAL INDUSTRY: ROLE OF MEDICAL AFFAIRS AND MEDICAL COMMUNICATIONS - Jain, Sonal (International Journal of Clinical and Biomedical Research, 2017)
The launch of a new drug into the market requires a unique and complex process initiating from development (R&D) to its commercialization (marketing authorization and selling of these products). Due to increased burden by regulatory authorities, the medical affairs evolved as separate medical organization to bifurcate medical and commercial functions. It is closely associated with development but works mainly on post-approval activities by providing both the scientific and clinical expertise. The core functional areas of medical affairs (MA) include: medical communications/publications, medical science liaisons (MSLs) and medical information. In the recent years ethical and evidence-based medical communications has attained increasing importance in emerging pharmaceutical markets. A successful product launch is based on both promotional (medico-marketing) and non-promotional (medical information services, publications) material to support the product and to report clinical trials in peer-reviewed international journals. Local clinical or observational studies and medical surveys can provide sufficient information about the product. Besides, a number of medical communication like product monographs, brochures, slide kits, leave behind literature (LBL), continuous medical education (CME) slides, training modules, key opinion leader documents(promotional inputs) and conference posters, abstracts, and journal articles (research based inputs)are other ways to aid in an effective product launch. In the last 10 years medical writers in India have developed the capability to meet this challenge through their training and work experience making India hub for medical communications services. KEYWORDS: Key opinion leaders; Medical affairs; Medical communications; Medical science liaisons; Medical writing.